The Relationship Between The Role Of Parents In Media Access To Adolescent Sexual Behavior In Sma 6 Takengon, Silih Nara District, Aceh Central District Year 2020 - Rosmani Sinaga (Institute of Computer Science (IOCS), 2021)
Indonesian Adolescent Reproductive Health (SKRRI) explained that the level of knowledge of adolescents in 2007 about reproductive health was still low including 37.9% of adolescents who did not know about fertile days, 49 adolescents who stated that they did not know about sexual intercourse once could get pregnant. 3%, while 43.4% had never heard of sexually transmitted diseases. Lack of knowledge about reproductive health can lead adolescents towards free sex behavior which can cause transmission of sexually transmitted diseases and HIV/AIDS. In developing countries, as many as 40 percent of female and male adolescents aged 18 years have had free sex without being married. As a result of this premarital relationship, around 12 percent were positive for STIs, around 27 percent were HIV positive teenagers, and another 30 percent of young women were pregnant. Therefore, half of them still gave birth and the other half had abortions. Adolescent associations about free sex can be found through reports from the Health Service, in 2015 there were 1,078 school-age adolescents undergoing childbirth and 976 of them were pregnant outside of marriage, association tended for adolescents to have pregnancies outside of marriage. In the cities of Medan and Bandung, premarital sexual acts reached 52 percent, while in the city of Surabaya, it reached 47 percent. Data found by the National Commission for Child Protection found that 93.7 percent of teenagers in Indonesia had kisses, oral sex and even petting. The percentage of junior high school youth who are no longer virgins is 62.7 and 21.2% of vocational youth have had abortions and 97 percent have watched pornographic films.